Pendampingan Potensi Wisata Kearifan Lokal Batik Motif Khas Satwa Lampung di Desa Labuhan Ratu VII Lampung Timur - Salih Alimudin; Elsa Virna Renata; Elly L. Rustiati; Sunandar Sunandar; Basuki Rahmat (Jurnal Pengabdian Masyarakat Pinang Masak, 2021)
Abstract Labuhan Ratu VII is one of settlements next to Way Kambas National Park, and has experienced elephants – human conflict. Batik BARATA has developed wildlife motives such as sumatran elephants, tigers and rhinos.  It is potential for ecotourism packages and education as well as wildlife conservation in Lampung.  Its companionship were carried out by off and online from July 2019 - October 2020 under TFCA Sumatra UNILA-ALeRT Consortium program.  BARATA Batik becomes one great ecotourism attractant in Labuhan Ratu VII.   Keywords: Companionship, ecotourism, wildlife, Labuhan Ratu VII, TFCA Sumatera